MO432COMPARATIVE ANALYSIS OF INDIRECT IMMUNOFLUORESCENCE AND ENZYME-LINKED IMMUNOSORBENT ASSAYS FOR ANTI-PLA2R ASSESMENT IN PATIENTS WITH PRIMARY MEMBRANOUS NEPHROPATHY. (29th May 2021) - Galkina, Olga; Bogdanova, Evdokia; Zubina, Irina; Levykina, Elena; Smirnov, Alexei
Abstract: Background and Aims: Antibodies to M-type phospholipase A2 receptor (PLA2R-Ab) are considered to be a promising biomarker for laboratory diagnosis of primary membranous nephropathy (PMN) and may be useful in the evaluation of the response to therapy and CKD prognosis. The aim of the study was to compare two immunoassay methods – indirect immunofluorescence (IIF) and enzyme immunoassay (ELISA) for the determination of circulating PLA2R-Ab in patients with PMN. Method: The study included 54 patients aged 55 (40-63) yrs. (M: F [33:21]) with PMN before treatment (n=16) and treated with immunosuppressive therapy (IST) (n=38), and apparently healthy individuals of the corresponding gender and age (n=10). Proteinuria and estimated glomerular filtration rate (eGFR) were determined in all participants. The levels of PLA2R-Ab were determined by IIF and quantitative/ semi-quantitative ELISA (EURUIMMUN AG test, Germany). In 16 PMN patients without treatment and 28 PMN patients treated with IST the level of PLA2R-Ab was measured one time and in 10 PMN patients treated IST – in dynamic, from 2 to 5 times. Statistical comparisons among groups were performed using Mann–Whitney U-test and Kruskal-Wallis H tests. The association between variables was estimated using Spearman's coefficient. Sensitivity and specificity of the methods were calculated. Results: The correlation coefficient between IIF and ELISA was 0.82 (p <0.005). There were more PLA2R-Ab-positive cases detected by ELISA, both before treatment (ELISA - 80%, IIF - 67%) and among patients treated with IST (ELISA - 63%, IIF - 50%). In control group, ELISA showed no positive results for PLA2R-Ab (specificity was 100%). The levels of proteinuria and eGFR were associated with autoantibodies determined by ELISA, both quantitative and semi-quantitative (proteinuria: r = 0.69, p = 0.001; eGFR: r = -0.38, p = 0.035) but not by IIF (proteinuria: r=0.33, p=0.061; eGFR: r=-0.26, p=0.082). The levels of PLA2R-Ab measured by ELISA correlated with the course of disease in patients treated with IST, while IIF did not show any dynamics is some cases. Conclusion: Both quantitative and semi-quantitative ELISA were considered to be more preferable methods since the obtained results correlate with renal dysfunction and allow to assess the concentration of PLA2R-Ab in the course of disease more accurately, that may contribute to timely correction of treatment and improvement of outcome.